Delayed healing of a navicular stress fracture, following limited weight-bearing activity. (11th March 2014) - Robinson, Matthew; Fulcher, Mark
Abstract : This report describes a 21-year-old man, a semiprofessional football (soccer) player, with a navicular stress fracture. It highlights the difficulty in diagnosing the condition and the complications arising from inadequate management. The case discusses the optimal management of these stress fractures and the detrimental role of weight-bearing recovery. The diagnosis of navicular stress fractures is challenging, and a high index of suspicion is required. The available literature indicates that limited weightbearing is not an appropriate treatment for navicular stress injuries. Non-weight-bearing (NWB) cast immobilisation for 6–8 weeks appears to be the gold standard treatment; however, open reduction with internal fixation (ORIF) has similar success rates and an equal return-to-play time but should also be followed by a period of NWB. NWB cast immobilisation for 6 weeks remains a good second option at any time following failed limited weight-bearing activity.